Pembelajaran Teks Report dengan Proyek ’Cerdiq’ Berbasis Kinemaster - Amin Fajariyah, Laily (Jurnal Didaktika Pendidikan Dasar, 2018)
The research objective was to improve the tenth grade students’ report texts in English in semester 1 dan 2 in the Junior Secondary School 5 Panggang through “cerdig” project with Kinemaster basis. The learning steps consisted with topic selection, scripting and storyboarding, digitizing the elements, evaluating, and publishing. The significance of the project was to improve the students’ understanding in writing report texts in English. This was a Best Practice Research in writing. Data were collected through observation and analyzed descriptively and qualitatively. The results show that students were enthutiastic in participating in the activities as well as ability in monologue. The students’ creativity and skill in technology were improved.